From the Civil War to the apocalypse : postmodern history and American fiction - Parrish, Timothy, 1964- (University of Massachusetts Press, 2008)
"Recent postmodern theorists have argued that since history is a narrative art, it must be understood as a form of narrative representation analogous to fiction ... In addressing the postmodernist claim that history works no differently than fiction, Timothy Parrish rejects the implication that history is dead or hopelessly relativistic. Rather, he shows how the best postmodern novelists compel their readers to accept their narratives as true. These novelists write history as a form of fiction ... Parrish concludes that history, not identity, is the ground of postmodern American fiction"--Publisher's description